2003
DOI: 10.1046/j.1475-097x.2003.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Poincaré plot indexes of heart rate variability capture dynamic adaptations after haemodialysis in chronic renal failure patients

Abstract: The hypothesis that the Poincaré plot indexes of heart rate variability (HRV) detect dynamic changes after haemodialysis (HD) over the HRV in haemodynamically stable chronic renal failure (CRF) patients was examined. Minor axis (SD1), major axis (SD2) and the SD1/SD2 ratio were compared against standard HRV indexes in time and frequency domain, in a group of healthy subjects and in a group of CRF patients before and after HD. These indexes were estimated from Poincaré plots reconstructed with lags of one, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(47 citation statements)
references
References 32 publications
3
43
0
1
Order By: Relevance
“…The concept of this m lagged plot emerged from the recognition that any given R-R interval can influence up to eight subsequent R-R intervals 24,25 . It has been shown that SD1 correlates with the short-term variability of heart rate and is mainly influenced by parasympathetic modulation, whereas SD2 is a measure of long-term variability 14,26 and reflects sympathetic activation.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of this m lagged plot emerged from the recognition that any given R-R interval can influence up to eight subsequent R-R intervals 24,25 . It has been shown that SD1 correlates with the short-term variability of heart rate and is mainly influenced by parasympathetic modulation, whereas SD2 is a measure of long-term variability 14,26 and reflects sympathetic activation.…”
Section: Discussionmentioning
confidence: 99%
“…The mean value of SD 1 for Poincare plot in Fz, Cz and Pz channels with two different lags (1)(2)(3)(4)(5)(6) are shown in Table 1. The values of SD 1 with lag 1 are about 1.53 -1.94, but they are at around 8.52 -10.95 with lag 6 in all channels.…”
Section: Resultsmentioning
confidence: 97%
“…The conventional plot has two dimensions and a lag of one interval, i.e., each point on the plot consists of a pair of successive intervals (RR i , RR i+1 ). Lerma et al [6] used longer lags (RR i , RR i+t with 1  t  8) to analyze HRV in chronic renal failure patients. Contreras et al [4] showed that lagged Poincare widths and spectral indices might be useful to distinguish normal from pathological heart rate signals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been often used to portray the dynamics of fluctuations between the intervals, such as in the studies of beat-to-beat heart rate variability [1517]. We generated Poincaré sections by plotting the intersections of a given trajectory in the phase space diagram with a lower-dimensional state subspace, called the Poincaré plane, transverse to the trajectory [18, 19].…”
Section: Methodsmentioning
confidence: 99%